Prognostic effect of incongruous lymph node status in early-stage non-small cell lung cancer. Issue 2 (February 2021) - Chen, Jian-Xun; Lu, Ting-Yu; Lin, Yu-Sen; Fang, Hsin-Yuan; Shih, Pin-Keng
Abstract: Introduction: Tumor recurrence is an important issue for patients with stage I non-small cell lung cancer (NSCLC) and adjuvant therapy is considered of no benefit to a tumor less than 4 cm. The purpose of this study was to evaluate the impact of positron emission tomography/computed tomography (PET/CT) on tumor recurrence in patients with a completely resected pN0 NSCLC less than 4 cm. Methods: Between January 2011 and December 2016, 211 consecutive patients with diagnoses of stage I NSCLC less than 4 cm after complete resection were included. The maximum of standard uptake value (SUVmax) of primary tumor and the presence of positive lymph nodes on PET/CT scans were documented. Disease-free survival was evaluated by the Kaplan-Meier method and recurrence risk factors were identified by univariable and multivariable analyses. Results: Patients with positive lymph nodes on PET/CT had a lower 5-year disease-free survival (37.6% vs 72.7%, p  < 0.001). Multivariable analysis demonstrated that the tumor SUVmax >2.93, the presence of positive lymph nodes on PET/CT, and poor differentiation were significant factors for tumor recurrence. Patients with the tumor SUVmax >2.93 and positive lymph nodes on PET/CT simultaneously had 5.33-fold increase in the risk of recurrence ( p  < 0.001). Conclusion: The presence of positive lymph nodes on PET/CT scans can be a good indicator in predicting patients with high risk of developing recurrence in pN0 NSCLC less than 4 cm. This result helps identify patients likely to benefit from adjuvant therapy.